Combination of valproic acid and morpholino splice-switching oligonucleotide produces improved outcomes in spinal muscular atrophy patient-derived fibroblasts. (September 2017) - Farrelly-Rosch, Anna; Lau, Chew Ling; Patil, Nitin; Turner, Bradley J.; Shabanpoor, Fazel
Abstract: Spinal muscular atrophy (SMA), the leading genetic cause of infant mortality worldwide, is characterised by the homozygous loss of the survival motor neuron 1 ( SMN1) gene. The consequent degeneration of spinal motor neurons and progressive atrophy of voluntary muscle groups results in paralysis and eventually premature infantile death. Humans possess a second nearly identical copy of SMN1, known as SMN2. However, SMN2 produces only 10–20% functional SMN protein due to aberrant splicing of its pre-mRNA that leads to the exclusion of exon 7. This level of SMN is insufficient to rescue the phenotype. Recently developed splice-switching antisense oligonuclotides (SSO) have shown great promise in correcting the aberrant splicing of SMN2 towards producing functional SMN protein. Several FDA approved drugs are being repurposed for SMA treatment including valproic acid (VPA), a histone deacetylase inhibitor, which has been shown to increase overall SMN2 expression. In this study, we have characterised the effects of single and combined treatment of VPA and a SSO based on phosphorodiamidate morpholino oligomer (PMO) chemistry. We conjugated both VPA and PMO to a single cell-penetrating peptide (Apolipoprotein E (ApoE)) for their simultaneous intracellular delivery. Treatment of SMA Type I patient-derived fibroblasts with the conjugates showed no additive increase in the level of full-length SMN2 mRNA expression over both 4 and 16 h treatments indicating that conjugation of VPA to ApoE-PMO has limited benefit. However, treatment with a combination of VPA and ApoE-PMO induced more favourable splice switching activity than either agent alone, promoting exon 7 inclusion in SMN2 transcripts. Our results suggest that combination therapy of VPA and ApoE-PMO is superior in upregulating SMN2 production in vitro, as compared to singular treatment of each compound at both transcriptional and protein levels. This study provides the first indication of a novel dual therapy approach for the potential treatment of SMA. Graphical abstract: Highlights: Antisense oligonuclotides (ASO) and Valproate increased protein in Spinal Muscular Atrophy patient-derived fibroblast. Conjugation of VPA to peptide-ASO for simultaneous intracellular delivery is not therapeutically favourable. Combination therapy of VPA and peptide-ASO is superior compared to singular treatment of each compound. Combination of VPA and peptide-ASO is not toxic at a therapeutically relevant concentrations. This dual therapy approach represent a potential treatment for Spinal Muscular Atrophy patients.